Formal institutions, informal institutions and entrepreneurial activity: A comparative relationship between rural and urban areas in Colombia - Diana Marcela Escandón-Barbosa; David Urbano; Andrea Hurtado-Ayala; Jairo Salas Paramo; Alvaro Zapata Dominguez (Journal of Urban Management, 2019)
The study of the impact of institutions on entrepreneurship has been a topic of great interest in recent years. Nevertheless, less attention has been paid to the relation that can exist between the spatial context and the entrepreneurial activities. Specifically, institutions and the space of entrepreneurial activities in a country have rarely been considered as a whole. This paper attempts to bridge the gap between these two aspects and seeks to examine the entrepreneurial activity in rural areas in comparison with urban areas based on the formal and informal institutions in an emerging economy such as Colombia. It claims that the formal institutions affect rural and urban entrepreneurs differently, examining the moderating effect of the informal institutions on this relation. Using a hierarchical logic model with panel data, 30 cities in Colombia over the period 2000-2013 are used as samples to explore the differences between rural and urban areas. It is found that the informal institutions achieve greater influence in the rural areas; these areas are favored to a greater extent by the social norms, since they are smaller territories with greater integration between citizens. However, the existence of subjective and objective insecurity affects rural entrepreneurial activity in a wider scope than urban entrepreneurial activity, decreasing the creation of new ventures.
Keywords: 710; Entrepreneurship; Formal and informal institutions; Rural areas; Urban areas